Supplementation of snake-head fish bone powder for making cookies - Abu B. Talawi; Almerdian Almerdian; Andi R. Ramli; Metusalach Metusalach; Nandi K. Sukendar (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2019)
Snake-head fish bone is one of industrial fish processing waste which can beused as a mineral source. However, the utilisation of fish bones in foodproducts has not been optimized. The aim of this research was to utilizeSnake-head fish bone for making cookies and to evaluate their chemicalproperties and sensory acceptability of the product. Snake-head fish bone wasfirst steamed, dried, milled into powder then mixed with wheat flour andother additional ingredients. The result showed that cookies which made fromSP-318 formula (20% Snake-head fish bone powder and 80% wheat flour)were the best result for all sensory attributes. It presented like moderately forthe hedonic score. Protein, ash moisture, carbohydrate, and fat contents of theSP-318 formula were 10.77%, 8.10%, 9.25 %, 44.23%, and 7.65%, Overall,this study clearly showed that it was possible to make cookies whichsupplemented by Snake-head fish bone powder and the product did not haveany negative results on sensory attributes.